2022
DOI: 10.1111/jfbc.14093
|View full text |Cite
|
Sign up to set email alerts
|

Does nano‐curcumin supplementation improve hematological indices in critically ill patients with sepsis? A randomized controlled clinical trial

Abstract: Sepsis is the final common pathway to death for severe infectious diseases worldwide. The present trial aimed to investigate the effects of nano‐curcumin supplementation on hematological indices in critically ill patients with sepsis. Fourteen ICU‐admitted patients were randomly allocated into either nano‐curcumin or placebo group for 10 days. The blood indices, serum levels of inflammatory biomarker and presepsin as well as nutrition status, and clinical outcomes were assessed before the intervention and on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Nanocurcumin formulation in COVID-19 patients led to reduced levels of GM-CSF, IFNγ, IL-1β, IL-6, IL-17, IL-18, IL-21, IL-23, RORγ t, T-box transcription factor 21 (TBX21), and TNF-α, and induced FOXP3, IL-4, IL-10, IL-35, and TGF-β levels. It also improved lymphocyte count, oxygen saturation levels, symptoms, and Treg cell frequency and reduced symptom resolution time, hospitalized duration, and mortality rate in COVID-19 patients. ,, Several studies have also revealed the beneficial effects of nanocurcumin formulation in treating critically ill patients with sepsis. Nanocurcumin from Exir-Nano-Sina (Iran) suppressed Bcl-2, inflammatory molecules such as ICAM-1, IL-1β, IL-6, IL-18, TLR-4, TNF-α, and VCAM-1, creatinine, lipid profile, liver enzymes and reduced mechanical ventilation period in these patients. ,, In addition, nanocurcumin treatment enhanced clinical response rate and ameliorated radiation-induced dermatitis in various cancers including bladder, head and neck, and prostate cancers. ,, It also reduced DNA damage and micronuclei formation in lymphocytes of thyroid cancer patients . Moreover, the antidiabetic properties of nanocurcumin were attributed their capacity in reducing FBG, glycated Hb, insulin, hs-CRP, TC, TAC, TN, LDL-C, VLDL-C, TC/HDL-C, MDA, and augmented insulin sensitivity, TAC, peroxisome proliferator-activated receptor gamma (PPARγ), LDLR, and GSH levels in T2D patients. It also suppressed neuropathy, depression, and anxiety in T2D-associated peripheral neuropathy patients. , Nanocurcumin supplementation for 10 weeks improved sperm count, sperm motility, and testosterone levels in patients with infertility complaints .…”
Section: Curcumin Formulationsmentioning
confidence: 97%
“…Nanocurcumin formulation in COVID-19 patients led to reduced levels of GM-CSF, IFNγ, IL-1β, IL-6, IL-17, IL-18, IL-21, IL-23, RORγ t, T-box transcription factor 21 (TBX21), and TNF-α, and induced FOXP3, IL-4, IL-10, IL-35, and TGF-β levels. It also improved lymphocyte count, oxygen saturation levels, symptoms, and Treg cell frequency and reduced symptom resolution time, hospitalized duration, and mortality rate in COVID-19 patients. ,, Several studies have also revealed the beneficial effects of nanocurcumin formulation in treating critically ill patients with sepsis. Nanocurcumin from Exir-Nano-Sina (Iran) suppressed Bcl-2, inflammatory molecules such as ICAM-1, IL-1β, IL-6, IL-18, TLR-4, TNF-α, and VCAM-1, creatinine, lipid profile, liver enzymes and reduced mechanical ventilation period in these patients. ,, In addition, nanocurcumin treatment enhanced clinical response rate and ameliorated radiation-induced dermatitis in various cancers including bladder, head and neck, and prostate cancers. ,, It also reduced DNA damage and micronuclei formation in lymphocytes of thyroid cancer patients . Moreover, the antidiabetic properties of nanocurcumin were attributed their capacity in reducing FBG, glycated Hb, insulin, hs-CRP, TC, TAC, TN, LDL-C, VLDL-C, TC/HDL-C, MDA, and augmented insulin sensitivity, TAC, peroxisome proliferator-activated receptor gamma (PPARγ), LDLR, and GSH levels in T2D patients. It also suppressed neuropathy, depression, and anxiety in T2D-associated peripheral neuropathy patients. , Nanocurcumin supplementation for 10 weeks improved sperm count, sperm motility, and testosterone levels in patients with infertility complaints .…”
Section: Curcumin Formulationsmentioning
confidence: 97%
“…Curcumin is remarkable bioactive polyphenol extracted from the rhizome of turmeric (Curcuma longa) [ 9 , 10 ]. Curcumin has a wide range of medicinal effects such as hepatoprotective, antimicrobial, anti-inflammatory, antioxidant, and antitumor activities [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This combat in turn causes extensive coagulation and inflammatory responses in the body. 2,3 During sepsis, the dysregulation or overreaction of the immune system with the purpose of elimination of pathogens can ultimately lead to tissue damage, organ failure, and death. 4 According to global statistics, the prevalence of sepsis is estimated to be more than 30 million cases in the world each year, which has increased by 9 to 13 percent annually.…”
Section: Introductionmentioning
confidence: 99%